BAUXITE RESOURCE ESTIMATION IN BLOCK 2 AT PT. ANUGRAH BORNEO MARUYA PERSADA, KETAPANG REGENCY, KALIMANTAN BARAT PROVINCE - Ceuputra, David Pranasetyo; Syafrianto, M. Khalid; Mukhtar, Wahdaniah (Jurnal Teknik Sipil, 2024)
According to the Mineral Commodity Analysis and Evaluation Team of the International Mineral Information Center Development Project (1983), bauxite is an alumina ore used in industrial applications and as a primary material in aluminum production. Bauxite deposits are abundant in West Kalimantan. PT. Anugerah Borneo Maruya Persada, a mining company located in Deranuk Village, Jelai Hulu District, Ketapang Regency, focuses on bauxite extraction. Due to high market demand, the company seeks to identify new resources, necessitating an estimation of potential bauxite resources. This study evaluates the bauxite resources in Block 2 of PT. Anugrah Borneo Maruya Persada using the Area of Influence (AOI) polygon-included method. The bauxite volume is calculated by determining the area of influence and multiplying it by the deposit thickness. A test pit spacing of 50 meters and a cut-off grade of â‰¥35% were used to assess deposit distribution. Results show high-grade bauxite at 10 test pits, medium-grade at two pits, and low-grade at six pits, with deposits spreading from west to east. The total estimated bauxite volume in Block 2 is 66,250 m ³ or 106,000 tons.